2015
DOI: 10.1086/679485
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in Resistance to Desiccation and Heat Shock Protein Expression in the Land SnailTheba pisanaalong a Climatic Gradient

Abstract: Land snails frequently encounter desiccating conditions, and their survival depends on a suite of morphological, physiological, and molecular adaptations to the specific microhabitat. Strategies of survival can be determined by integrating information from various levels of biological organization. In this study, we used a combination of physiological parameters related to water economy and molecular factors (stress protein expression) to investigate the strategies of survival adopted by seven populations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
3
15
1
1
Order By: Relevance
“…Thus, our study is consistent with previous comparative studies of ectothermic species from different habitats demonstrating a direct relationship between habitat temperature and thermotolerance (Sorte and Hofmann 2005;Stillman and Somero 2000). Importantly, our findings for thermal tolerance limits are consistent with the general hierarchy of desiccation resistance, where the populations of Akko, Achziv, and Kiryat Yam were the most desiccation-resistant, the populations of Ashkelon and Or Akiva were the least resistant, and the Ashdod population having an intermediate response to desiccation stress (Mizrahi et al 2015).…”
Section: Discussion Thermal Tolerancesupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, our study is consistent with previous comparative studies of ectothermic species from different habitats demonstrating a direct relationship between habitat temperature and thermotolerance (Sorte and Hofmann 2005;Stillman and Somero 2000). Importantly, our findings for thermal tolerance limits are consistent with the general hierarchy of desiccation resistance, where the populations of Akko, Achziv, and Kiryat Yam were the most desiccation-resistant, the populations of Ashkelon and Or Akiva were the least resistant, and the Ashdod population having an intermediate response to desiccation stress (Mizrahi et al 2015).…”
Section: Discussion Thermal Tolerancesupporting
confidence: 91%
“…In our previous study, we found that the ability of T. pisana snails to cope with desiccating conditions was correlated with habitat temperature but not with the rainfall gradient (Mizrahi et al 2015). Our present study in T. pisana demonstrates also a positive correlation between habitat temperature and thermal tolerance, suggesting that temperature plays important roles in determining the ability of T. pisana snails to cope with environmental stress conditions of both heat and aridity.…”
Section: Discussion Thermal Tolerancesupporting
confidence: 52%
See 3 more Smart Citations